Activities of jamu and spices on adipocytes formation - M., Taher; Abdul Majid, Fadzilah Adibah; Sarmidi, Mohd Roji (2006)
Jamu is a traditionally formulated herbs being used as traditional medicines for years to treat illnesses in the region of Indonesia and Malaysia. Different formulations are claims by the traditional healers/practitioners to cure or control many metabolic diseases such as hypertension, diabetes, cancer, stroke etc. In attempt to discover the activity of these traditional medicines that could promote adipogenesis, we investigated the ability of Jamu KM (traditional herbal preparation recommended for diabetes sufferers) extracts to stimulate 3T3-L1 preadipocytes. Extracts from Indonesian bay leaf (Eugenia polyantha) and cinnamon (Cinnamomum zeylanicum) which are previously claimed by scientific papers are also compared. In this study, we designed an experiment by replacing insulin with those extracts. The differentiated of 3T3-L1 adipocytes were monitored using oil red O staining method. Induction of adipocyte formation by those extracts gave the similar effects to insulin activity in adipogenesis.